The relationship of information systems in the decision-making catalog of professional sports clubs - oucif nor elhoda; youcef ouahab; بن نور معمر (sports creativity, 2025)
The study aimed to reveal the relationship between information systems and decision catalog in the light of the application of the marketing activities of obstacles facing the decision makers, through the descriptive approach addressing for route flooding on nature in order to do that we use the information systems scale giffen marketing engine trouble forced the prestige 2004 gauge and obstacles to marketing activities to his companion Tarek Ali Belhadj, 2007 and built a questionnaire to measure the adoption of the resolution, where these standards were applied to a sample of Ahli club tower and ES Setif and then we using statistical program packets in the twenty-first